2009
DOI: 10.1111/j.1469-7610.2009.02158.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and attachment influences on adolescents’ regulation of autonomy and aggressiveness

Abstract: The study suggests a gene-attachment interaction in adolescents where the adolescent's attachment status moderates a genetically based higher negative reactivity in response to threats to autonomy in social interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
80
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 53 publications
11
80
0
2
Order By: Relevance
“…Here, the effect of attachment at 4 years of age only came out significant with parent reports. Given that previous studies have reported Attachment ϫ 5-HTTLPR effects in preschoolers (Kochanska et al, 2009) and adolescents (Starr et al, 2013;Zimmermann et al, 2009), our mixed GXE results at 6 years of age may be methodological rather than substantial. Notwithstanding, our results discerned a main effect of the SS genotype on emotion regulation at 8 years of age.…”
Section: Differential Susceptibility and 5-httlprmentioning
confidence: 84%
See 1 more Smart Citation
“…Here, the effect of attachment at 4 years of age only came out significant with parent reports. Given that previous studies have reported Attachment ϫ 5-HTTLPR effects in preschoolers (Kochanska et al, 2009) and adolescents (Starr et al, 2013;Zimmermann et al, 2009), our mixed GXE results at 6 years of age may be methodological rather than substantial. Notwithstanding, our results discerned a main effect of the SS genotype on emotion regulation at 8 years of age.…”
Section: Differential Susceptibility and 5-httlprmentioning
confidence: 84%
“…As a result, attachment security, as an environmentally induced regulatory mechanism, could be especially important for the development of emotion regulation among more reactive S carriers. In fact, S carriers have been found to be most affected by their attachment styles with regard to self-regulation in preschool (Kochanska et al, 2009), as well as autonomy and aggression (Zimmermann, Mohr, & Spangler, 2009) and stress and depression (Starr, Hammen, Brennan, & Najman, 2013) in adolescence. Whereas the research by Kochanska et al (2009) proved consistent with the diathesisstress model, the work of Starr et al (2013) and Zimmermann et al (2009) appears more consistent with differential-susceptibility theorizing.…”
Section: The Moderating Role Of 5-httlprmentioning
confidence: 99%
“…Vergleichbare Zusammenhänge zwischen Bindungsunsicherheit und internalisierenden Symptomen wurden auch für die späte Kindheit und das Jugendalter bestätigt (Brumariu u. Kerns, 2010). Ebenso für Zusammenhänge zwischen unsicherer Bindung, insbesondere Bindungsdesorganisation, und externalisierenden Symptomen bei Kindern von der frühen bis zur mittleren Kindheit (Fearon, Bakermans-Kranenburg, van IJzendoorn, Lapsley, Roisman, 2010;Lyons-Ruth u. Jacobvitz, 2008;O'Connor, Collins, Supplee, 2012 (Collins, Madsen, Susman-Stillmann, 2002 (Zimmermann, Mohr, Spangler, 2009). Das Bindungsinterview bildet also die aktuelle Beziehungsqualität und erlebte emotionale Unterstützung sowie die verinnerlichte bisherige Bindungsgeschichte ab.…”
Section: Bindung Als Einflussfaktor Auf Die Entwicklung Von Verhaltenunclassified
“…2 Accumulating evidence supports the view that the inefficient S allele of 5-HTTLPR in combination with secure attachment increases the likelihood of agreeable yet autonomous social behaviour in adolescents. 3 The same polymorphism, in combination with insecure parenting, predicts poor self-regulation 4 and impulsiveness in response to threats to autonomy. 3 The challenging suggestion is that certain apparent genetic vulnerabilities are retained in the gene pool because under favourable circumstances they enhance social sensitivity, potentially making a child both more and less pro-social, depending on their social environment.…”
mentioning
confidence: 99%
“…3 The same polymorphism, in combination with insecure parenting, predicts poor self-regulation 4 and impulsiveness in response to threats to autonomy. 3 The challenging suggestion is that certain apparent genetic vulnerabilities are retained in the gene pool because under favourable circumstances they enhance social sensitivity, potentially making a child both more and less pro-social, depending on their social environment. It may be interesting to note that 'collectivistic' nations, such as Korea or China, appear to have a higher prevalence of S-allele carriers than nations, such as most western countries, where individualism is more highly valued.…”
mentioning
confidence: 99%